The ecological point of view could complicate the attempt to create a halophytes database? The Romanian story - Marius-Nicuşor, Grigore (Ecological Questions, 2011)
In this paper we discuss some inherent difficulties occurring when we tried to realize a Romanian halophytes database. We are focusing here especially on the way in which the ecological approach of halophytes could facilitate or complicate this attempt. Our previous experience, as well the prospective improvements in this regard are considered.